(untitled) (Majalah Ilmiah UNIKOM, 2020)
LPPM is an institution at the university, it can be said that LPPM is a knowledge mine for academic community research activities. The function of LPPM continues to grow not only as a place to publish research works, but also as a place for knowledge to be explored. Non-print sources such as electronic journals and information that can be accessed through web media. The need for this information requires information technology support that can help LPPM place various knowledge references for researchers, lecturers, students, and others to gain quality knowledge by accessing research journals managed by LPPM. With the presence of KMS, it can certainly help in gathering, identifying potential knowledge, and managing overall knowledge. and can be used to speed up decision making on problems that have been experienced before. by using the 10 steps tiwana amrit framework. the results of this study will produce an architectural blueprint design which can later be used as a reference for the implementation of program development or subsequent development. Key words: LPPM, Knowledge Management System, Architecture Design, Blueprint